On μ-invariants of Selmer groups of some CM elliptic curves - Aribam, Chandrakant (International journal of number theory, 2013)
We show that the Selmer groups defined over the cyclotomic ℤ3-extension of the field of 3-torsion points of the CM elliptic curves 256a1, 256a2, 256d1, 256d2, 121b1, 121b2 have μ-invariant equal to zero, verifying a conjecture in non-commutative Iwasawa theory.
Gesehen am 20.10.2020